Eseista czy historyk? O historiograficznej strategii Pawła Jasienicy - Bytner, Jarosław (Slavia Occidentalis, 2011)
The article discusses the problems of the relations between the literariness and history in Paweł Jasienica’s (Leon Lech Beynar) essays. The first part of the publication presents the author’s programme declarations connected with the choice of belles-lettres technique as the way of narrating history and the choice of an essay as the most suitable form of expression. The second part of the article includes reflections upon the presence of history in Jasienica’s essayistics as well as the essence of the selected disputes between the writer and professional historians from the period of the Polish People’s Republic (Polish abbr. PRL). The rhetoric element of Jasienica’s essays, although apparently diminished the significance of the scholarly studies and made them a specifically concealed trend in his literary works, was definitely not meant to be an attempt against history as a discipline of science. Jasienica’s historiographic strategy, despite the primacy of belles-lettres so often declared by the author of Polska Piastów (“Piast Poland”), consisted also in the constant promotion of scholar history.